Avaliação de ligações em madeira em estruturas de coberturas antigas por técnica termográfica - Cézar Augusto Silvino Figueredo (2016)
The conservation of the constructive elements of the roof is essential for stability and maintenance of the body of the building, since that protects against weathering and promotes anchorage of structural masonry. The roof also ensures the safety and physical integrity of the users of the building and an integral part of cultural heritage. Although there are significant technical books and manuals referring to the restoration published roof structures it is important to investigate the origins of the pathology and which less intrusive diagnostic methods. This research aims to use the active thermography technique as a nondestructive test for diagnosis of pathologies on roofs in old buildings in wood structure. For that tests were carried out in the laboratory and in the field, carrying out heating of the old wood and its thermal imaging. From the obtained thermograms, we observed heterogeneity in the surface temperature of the parts, featuring pathology. The results demonstrated the feasibility of using the technique as a primary diagnostic tool of hidden pathologies in wooden structures.